2014
DOI: 10.1002/eji.201445114
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for ineffective T‐cell responses to MHC anchor residue‐improved “heteroclitic” peptides

Abstract: MHC anchor residue-modified “heteroclitic” peptides have been used in many cancer vaccine trials and often induce greater immune responses than the wild-type peptide. The best-studied system to date is the decamer MART-1/Melan-A26–35 peptide, EAAGIGILTV, where the natural alanine at position 2 has been modified to leucine to improve human leukocyte antigen (HLA)-A*0201 anchoring. The resulting ELAGIGILTV peptide has been used in many studies. We recently showed that T cells primed with the ELAGIGILTV peptide c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
71
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 49 publications
3
71
0
Order By: Relevance
“…Our structural analysis demonstrated that, again, even single peptide substitutions outside of the main interaction interface could have a substantial impact on TCR binding affinity and T-cell antigen potency, consistent with our previous data (9, 15, 16). These observations add further evidence to our recent findings (19, 3134) that peptide presentation by MHCI can be dynamic and difficult to predict.…”
Section: Discussionsupporting
confidence: 85%
“…Our structural analysis demonstrated that, again, even single peptide substitutions outside of the main interaction interface could have a substantial impact on TCR binding affinity and T-cell antigen potency, consistent with our previous data (9, 15, 16). These observations add further evidence to our recent findings (19, 3134) that peptide presentation by MHCI can be dynamic and difficult to predict.…”
Section: Discussionsupporting
confidence: 85%
“…A) and α24β17 TCRs in complex with A2‐AAG was similar to the MEL5‐A2‐EAA complex. This was reflected by similar crossing angles of 48° and 42.3° and buried surface areas (BSAs) of ≈2200 and ≈2600 Å for MEL5 and α24β17 TCRs, respectively, in complex with A2‐AAG (Table ), compared to a crossing angle of 46.9° and BSA of 2366 Å for MEL5‐A2‐EAA .…”
Section: Resultsmentioning
confidence: 70%
“…In principle, the analysis could detect additional complexities, such as partial/multi-step dissociation, register-shifting, or multi-mode binding. Partial dissociation has been implicated in peptide immunogenicity (Duan et al, 2014) and in facilitating optimal T cell receptor binding (Madura et al, 2015). Register shifting or multi-mode binding has been seen in peptides that bind both class I and class II MHC proteins (Borbulevych et al, 2007; Landais et al, 2009; Günther et al, 2010).…”
Section: Discussionmentioning
confidence: 99%